Citrus aurantium L. extract alleviate depression by inhibiting gut microbiota-mediated inflammation in mice - Tao Li; Guirong Zeng; Lingfeng Zhu; Yanyang Wu; Qun Zhang; Fuhua Fu; Donglin Su; Gaoyang Li; Qili Li; Yang Shan (Food Science and Human Wellness)
Gut microbiota plays a crucial role in the pathophysiology of depression. This study aimed to explore the antidepressant effect of mature whole Citrus aurantium fruit extract (FEMC) in the chronic unpredictable mild stress (CUMS) model. The behavioral tests were applied to assess antidepressant effect and 16S rRNA sequencing was used to analyze the changes of gut microbiota. The results showed that the major components of FEMC were naringin and neohesperidin and significantly increased the sucrose preference index of the mice. FEMC also could reduce the feeding latency in an open field test and the rest time in a novelty suppressed feeding test. In addition, FEMC could increase CUMS-induced reduction in the levels of BDNF, PSD95, and SYN in the hippocampus. Moreover, FEMC intervention slightly decreased the ratio of Firmicutes to Bacteroidota. Meanwhile, FEMC reduced the abundance of the Prevotellaceae_Ga6A1_group, [Ruminococcus]_torques_group, which have been reported to be closely related to inflammation. Bioinformatics analysis revealed that mitogen-activated protein kinase (MAPK) signaling pathway and lipopolysaccharide biosynthesis were involved in the anti-inflammatory effect of FEMC in the CUMS animal model. Finally, the ELISA results showed that FEMC could significantly reduce the expression of pro-inflammatory cytokines IL-6 and TNF-α in the serum of depressive mice. Our results suggest FEMC can ameliorate depressive behavior by inhibiting gut microbiota-mediated inflammation in mice.